2020
DOI: 10.1101/2020.12.11.421305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heavy metal pollutants have additive negative effects on honey bee cognition

Abstract: Environmental pollutants can exert sublethal deleterious effects on animals. These include disruption of cognitive functions underlying crucial behaviours. While agrochemicals have been identified as a major threat to pollinators, other compounds, such as heavy metals that are often found in complex mixtures, have largely been overlooked. Here, we assessed the impact of acute exposure to field-realistic concentrations of lead, copper, arsenic, and their combinations, on honey bee learning and memory. All treat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This is consistent with studies reporting indiscriminate visits on metal-contaminated flowers [19,31,56]. At these realistic concentrations, metal pollutants alter the development [15], learning and memory [51,52], the metabolism [16,17] and antioxidative responses [57].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with studies reporting indiscriminate visits on metal-contaminated flowers [19,31,56]. At these realistic concentrations, metal pollutants alter the development [15], learning and memory [51,52], the metabolism [16,17] and antioxidative responses [57].…”
Section: Discussionsupporting
confidence: 87%
“…Pollinators are impacted by metal pollutants [5,18,51,52]. Here we showed that bees have only a limited capacity to detect and avoid these poisons in food.…”
Section: Discussionmentioning
confidence: 91%
“…learning score) or during memory retrieval (i.e. memory score) (Monchanin et al, 2020; see details below). Exposed and control bumblebees were always conditioned in parallel.…”
Section: Conditioning Experimentsmentioning
confidence: 99%